Explore the Impact of Technology on Chinese Student Academic Misconduct (Asian Education Studies, 2021)
This article discusses the relationship between students' honest behavior and science and technology from the perspective of science and technology. In the era of advanced science and technology, what strategies should schools take to prevent students' academic integrity. According to what reasons students choose to achieve higher academic achievement through academic misconduct, different methods are proposed to prevent students from academic misconduct. From the psychological point of view of three ways, education policy and high-tech means will effectively prevent cheating, so as to create a fair and just education environment.